The diameter of the acyclic Birkhoff polytope - Costa, Liliana (2008)
In this work we give an interpretation of vertices and edges of the acyclic Birkhoff polytope, , where T is a tree with n vertices, in terms of graph theory. We generalize a recent result relatively to the diameter of the graph .